The Phenomenon of Using OMI Social Media as a Means of Online Dating - Ade Fega Mei Lusi Ana; Sufyanto (Jurnal Spektrum Komunikasi, 2023)
This study concerns the phenomenon of using the online dating app OMI where we can get acquainted and date online. OMI is the latest online dating app, where women and men can do online dating activities through conversations, exploring various friendship relationships, and sexual desires. The theory used in looking at the phenomenon of using the OMI online dating application is Alfred Schutz's Phenomenology. The data mining used is qualitative research with a descriptive approach, which is research that focuses on the use of data that will be described in written and oral form based on the informants studied by conducting in-depth interviews with Generation Z in 1996-2009 in the sidoarjo and Surabaya areas. The results showed that the use of online dating applications aims as entertainment, finding a partner, expanding friendships. Teenagers who use online dating apps have an understanding of online dating through OMI social media as a positive and efficient thing in order to know the good and bad of online app users.